2017
DOI: 10.1021/acsphotonics.7b00206
|View full text |Cite
|
Sign up to set email alerts
|

Light-Directed Tuning of Plasmon Resonances via Plasmon-Induced Polymerization Using Hot Electrons

Abstract: The precise morphology of nanoscale gaps between noble-metal nanostructures controls their resonant wavelengths. Here we show photocatalytic plasmon-induced polymerization can locally enlarge the gap size and tune the plasmon resonances. We demonstrate light-directed programmable tuning of plasmons can be self-limiting. Selective control of polymer growth around individual plasmonic nanoparticles is achieved, with simultaneous real-time monitoring of the polymerization process in situ using dark-field spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 44 publications
0
99
0
Order By: Relevance
“…The authors were able to track the NP oscillations in real time by observing the spectral shift of the plasmonic resonance due to the change in the nanocavity width between the Au NP and the bulk Au substrate . In addition, in a similar experimental setup Ding et al demonstrated that the plasmon resonance of Au NPs could be controllably tuned by triggering a polymerization reaction within the gap between the NP and the Au substrate . In this experiment, the Au substrate was coated with a self‐assembled monolayer of thiophenol and Au NPs were then drop‐cast on top.…”
Section: Heating Up the Environmentmentioning
confidence: 96%
See 3 more Smart Citations
“…The authors were able to track the NP oscillations in real time by observing the spectral shift of the plasmonic resonance due to the change in the nanocavity width between the Au NP and the bulk Au substrate . In addition, in a similar experimental setup Ding et al demonstrated that the plasmon resonance of Au NPs could be controllably tuned by triggering a polymerization reaction within the gap between the NP and the Au substrate . In this experiment, the Au substrate was coated with a self‐assembled monolayer of thiophenol and Au NPs were then drop‐cast on top.…”
Section: Heating Up the Environmentmentioning
confidence: 96%
“…Thermoplasmonics is an emerging hot topic that offers a route to controllable actuation at the nanoscale and reversible plasmon tuning of sensing devices . The ability to manipulate nanoparticles in order to create and steer nanostructures is essential in many applications such as drug delivery, noninvasive microsurgery, nanoassembly, and fabrication …”
Section: Heating Up the Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that saturated polymers have also been generated locally on AuNPs. Polymerization took place even without initiators, implying plasmon initiation of free radicals via hot‐electron transfer to monomer at the Au surface …”
Section: Plasmonic Electrochemistrymentioning
confidence: 99%